Bandgap-dependent doping of semiconducting carbon nanotube networks by proton-coupled electron transfer for stable thermoelectrics - Hawkey, Angus; Rodríguez-Martínez, Xabier; Lindenthal, Sebastian; Jansen, Moritz C.F.; Crispin, Reverant; Zaumseil, Jana (Advanced electronic materials, 2025)
Networks of semiconducting single-walled carbon nanotubes (SWNTs) are a promising material for thermoelectric energy harvesting due to their mechanical flexibility, solution processability, high Seebeck coefficients and high electrical conductivities after chemical p- or n-doping. Here, we demonstrate that proton-coupled electron transfer (PCET) with benzoquinone (BQ) as the oxidant and lithium bis(trifluoromethylsulfonyl)imide (Li[TFSI]) for electrolyte counterions is a highly suitable method for p-doping of polymer-sorted semiconducting SWNT networks. The achieved doping levels, as determined from absorption bleaching, depend directly on both the pH of the aqueous doping solutions and the bandgap (i.e., diameter) of the nanotubes within the network. Fast screening of different nanotube networks under various doping conditions is enabled by a high-throughput setup for thermoelectric measurements of five samples in parallel. For small-bandgap SWNTs, PCET-doping is sufficient to reach the maximum thermoelectric power factors, which are equal to those obtained by conventional methods. In contrast to other doping methods, the electrical conductivity of PCET-doped SWNTs remains stable over at least 5 days in air. These results confirm PCET to be a suitable approach for more environmentally friendly and stable doping of semiconducting SWNTs as promising thermoelectric materials.